(untitled) (Physical Education, Health and Social Sciences, 2025)
Inguinal hernia repair is a common surgical procedure performed under either general anesthesia (GA) or spinal anesthesia (SA). The choice of anesthesia can significantly impact post-surgical recovery, including pain management, functional recovery, and complications. Understanding the comparative effectiveness of these anesthesia types is essential for optimizing patient outcomes. The objective of this study was to evaluate and compare the outcomes of GA versus SA in patients undergoing inguinal hernia repairs. A total of 113 patients undergoing inguinal hernia repairs at Ali Fatima Hospital, Lahore, were included in this descriptive observational study. Participants were administered either GA or SA. Post-surgery outcomes, including pain intensity (assessed using the Numeric Pain Rating Scale), functional recovery, complications (such as nausea, vomiting, and respiratory issues), and overall patient satisfaction were recorded. Data analysis was conducted using SPSS, with a chi-square test used to assess the association between anesthesia type and post-surgery pain. The study found significant difference in pain levels between GA and SA groups (p = 0.005). However, functional recovery was limited in both groups, with 78.8% unable to sit up unassisted and 74.3% unable to walk a few steps post-surgery. Respiratory complications were more common in GA patients (54%), while spinal headaches were noted in 57.5% of SA patients. Patient satisfaction was relatively high, with 62.8% feeling comfortable and pain-free during recovery. Both GA and SA are effective for inguinal hernia repair, with significant differences in pain outcomes. SA was associated with better pain control and quicker recovery, while GA was linked to more respiratory complications and nausea. Tailored anesthesia protocols are recommended for optimal patient care.